Выдающиеся крымскотатарские деятели музыкального искусства - Алиева, З. (Культура народов Причерноморья, 2013)
Outstanding Crimean Tatar musical figures have played a significant role in shaping the modern
musical art of the Crimean Tatars. Asan Refat – the first Crimean Tatar professional composer, social activist
and educator. He laid the foundation for harmonization and orchestration of the Crimean Tatar folk songs and
melodies. Refat took an active part in the ethnographic expeditions in collecting and recording folk music of the
Crimean Tatars. He worked closely with the scientific world . Wrote the first theoretical writings on music of the
Crimean Tatars. Asan Refat was the founder of the first Crimean Tatar Opera – "Chora Batyr". Publication
music collection "Sounds haytarma". Sherfedinov skillfully mastered the violin. At the end of the Moscow
Conservatory worked as music director of Simferopol Radio Committee. Written a number of musicals and
comedies. Composed a choral suite and a cantata for chorus. Sabriye Eredzhepova – the legendary Crimean
Tatar singer. She has participated in vocal competitions in Moscow. Her repertoire consisted not only of the
Crimean Tatar folk songs, but also songs of the peoples of the USSR and the works of the classical repertoire.
Sabriye Eredzhepova was the first soloist of the Crimean Tatar Song and Dance Ensemble "Haytarma". Her
book is an invaluable memories of the outstanding figures of the Crimean Tatar music. Ilyas Temirovich
Bakhshish – a talented composer, conductor, teacher and public figure . His musical career he began in the
Crimean radio committee . Bakhshish was prepared for publication by a number of musical works, including
choral and vocal works. He actively promoted the Crimean Tatar folk music on stages, radio and recorded it on
the plates . Bakhshish was the head of the Crimean Tatar ensemble "Haytarma". Arranged the Crimean Tatar
folk songs and melodies. Bakhshish published compilations of the Crimean Tatar songs. A great contribution to
the conservation of the cultural heritage of the Crimean Tatar makes Fevzi Aliyev – composer, folklorist and
singer. For several years he was the musical director and conductor of the State Song and Dance Ensemble
"Haytarma". He actively promoted among the young Crimean Tatar folk songs and melodies. The great
achievement of Fevzi Aliyev is the creation of "Anthology of the Crimean folk music". Noteworthy social and
educational activities F. Aliyev. Стаття присвячена видатним кримськотатарським музичним діячам. У статті
проаналізовано особливості їхньої музичної спадщини, показано їхня роль у формуванні сучасного
мистецтва кримських татар. Статья посвящена выдающимся крымскотатарским музыкальным деятелям. В статье
проанализированы особенности их музыкального наследия, показана их роль в формировании
современного музыкального искусства крымских татар.